Green synthesis of carbon nanospheres from Vachellia nilotica for pendimethalin removal - Vidhyarthi, Krupal; Priyadarshi, Gautam; Patel, Bhakti; Sahu, Santosh Kumar; Rami, Esha; Sahoo, Dipak Kumar; Patel, Ashish (Frontiers in Environmental Science, 2025)
Pendimethalin (PND), a persistent dinitroaniline herbicide, poses significant ecological and human health risks due to its high stability, bioaccumulation, and toxicity. The present study explores microwave-assisted rapid synthesis of carbon nanospheres (CNSs) from Vachellia nilotica biochar (VNBC) for the removal of PND from an aqueous medium. The synthesized CNSs were characterized in detail using Fourier-transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM)–energy dispersive X-ray spectroscopy (EDS), Brunauer–Emmett–Teller (BET), and pHZPC to confirm the oxygen-rich functional groups, crystalline graphitic domains, spherical morphology, elemental composition, surface area, and surface charge. A batch adsorption study was conducted to evaluate the effect of initial concentration (30 mg L-1–70 mg L-1), contact time (0 min–150 min), dose (2.5 mg–20 mg), and solution pH (2–12) at room temperature. The maximum removal efficiency (95.8%) and adsorption capacity (76.95 mg g-1) were achieved at 50 mg L-1 PND, pH 10, and a 50 mg dose of CNSs. Adsorption kinetics followed a pseudo-second-order model in linear fitting, while non-linear modeling indicated the dominance of physisorption with intraparticle diffusion, indicating a hybrid mechanism. Isotherm studies showed the Langmuir and Freundlich models best describe the adsorption process, confirming monolayer–multilayer adsorption. Furthermore, the presence of multivalent salts enhanced the removal efficiency through strong ionic bridging interaction and higher regeneration capacity up to five cycles, demonstrating potential toward real-water applicability. Compared to the conventional adsorbent, CNSs exhibited superior performance with rapid synthesis (3 min) and higher capacity. These findings establish biochar-derived CNSs as a cost-effective, eco-friendly, and efficient adsorbent for pesticide remediation in contaminated waters.